2023
DOI: 10.1002/ece3.10554
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat conditions drive uncertainty of risk and shape neophobic responses in Trinidadian guppies, Poecilia reticulata

Laurence E. A. Feyten,
Indar W. Ramnarine,
Grant E. Brown

Abstract: In response to uncertain risks, prey may rely on neophobic phenotypes to reduce the costs associated with the lack of information regarding local conditions. Neophobia has been shown to be driven by information reliability, ambient risk and predator diversity, all of which shape uncertainty of risk. We similarly expect environmental conditions to shape uncertainty by interfering with information availability. In order to test how environmental variables might shape neophobic responses in Trinidadian guppies (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 130 publications
0
1
0
Order By: Relevance
“…Recently, Feyten et al . (2023) demonstrated that Trinidadian guppies from pools with high structural complexity showed significantly more risk‐averse behaviour than conspecifics from lower complexity pools. Presumably, any habitat characteristic that conceals information about the environment should lead to incomplete cues.…”
Section: Informational Limitationsmentioning
confidence: 99%
“…Recently, Feyten et al . (2023) demonstrated that Trinidadian guppies from pools with high structural complexity showed significantly more risk‐averse behaviour than conspecifics from lower complexity pools. Presumably, any habitat characteristic that conceals information about the environment should lead to incomplete cues.…”
Section: Informational Limitationsmentioning
confidence: 99%
“…However, the effects of habitat complexity may differ. Trinidadian guppies, for example, exhibit higher levels of perceived predation risk in highly structured microhabitats (Feyten, 2023), likely due to limitations of visual risk assessment. Another environmental factor is ambient light levels, resulting from either diel cycles or shading.…”
Section: Factors Driving Availability Of Ecological Informationmentioning
confidence: 99%
“…The reef-driving behaviour of fish refers to the directional movement caused by their response to external stimuli [ 19 , 20 ]. Reef fish generally exhibit the instinctive behaviour of gathering around reefs, while their reef-driving behaviour is mainly characterized by first contact time [ 21 ], distribution rate [ 22 ], and related movement indicators [ 23 ]. First contact time can be quantified as the time initially needed for fish to approach a novel object, explained as the fear of fish towards new objects.…”
Section: Introductionmentioning
confidence: 99%